Penile Fracture: Delayed Presentation, Primary Urethral Repair and Satisfactory Outcome - Bashir Yunusa; Kalamon Wullie; Soeghen E. Willie; Solomane Konneh; Swaliho Sherriff; Ayun Cassell; Edit Ikpi (Case Reports in Urology)
Penile fracture is a relatively rare condition warranting emergency intervention. The commonest etiological factor remains coital activities, which explains why it is being underreported. Presentation is usually delayed and up to 38% of cases present with associated urethral injury. Prompt surgical intervention and primary urethral repair are associated with a good outcome. We present a 30-year-old male with unilateral penile fracture and associated urethral injury following sexual intercourse.